2010
DOI: 10.2340/16501977-0508
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive rehabilitation programmes in the chronic phase after severe brain injury: A systematic review

Abstract: Comprehensive rehabilitation programmes appear to be effective in terms of a reduction in psychosocial problems, a higher level of community integration and an increase in employment. Although this is the first review to differentiate between specific programmes, clear-cut clinical recommendations cannot yet be set out due to limited methodological quality and poor description of patient and intervention characteristics. Specific recommendations for future studies are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 29 publications
1
40
0
1
Order By: Relevance
“…Geurtsen and colleagues [9] stated that comprehensive rehabilitation in the chronic phase of severe brain injury was effective, and that day-treatment programmes had the highest level of evidence. Many of these were performed as group programmes and lasted several weeks, sometimes months, and often targeted behavioural problems.…”
Section: Acquired Brain Injury (Abi) Includes Traumatic Brain Injuriementioning
confidence: 99%
See 1 more Smart Citation
“…Geurtsen and colleagues [9] stated that comprehensive rehabilitation in the chronic phase of severe brain injury was effective, and that day-treatment programmes had the highest level of evidence. Many of these were performed as group programmes and lasted several weeks, sometimes months, and often targeted behavioural problems.…”
Section: Acquired Brain Injury (Abi) Includes Traumatic Brain Injuriementioning
confidence: 99%
“…However, few studies have explored the effects of such programmes [7]. Furthermore, even though there is a demand for more rigorous studies that evaluate the effects of such rehabilitation for ABI [9], not all questions regarding rehabilitation can be addressed by randomised controlled trials or a rigorous design [10]. It is also crucial to elucidate how pwABI experience different interventions, and how they themselves perceive their process 4 of rehabilitation.…”
Section: Acquired Brain Injury (Abi) Includes Traumatic Brain Injuriementioning
confidence: 99%
“…The percentage of pressure sores on admission and upon discharge showed that although there were large numbers on admission, an appropriate medical rehabilitation treatment and good nursing led to the discharge percentage being very low. 13,14 The findings in the present survey are compared with newly analyzed information for three previous large series: the International Data Bank involving the United Kingdom, the Netherlands, and the United States; the North American Traumatic Coma Data Bank; and data from four centers in the United Kingdom. The comparisons showed substantial similarities and also differences that may reflect variations in policies of admission of head injury to TBI rehabilitation units and the evolution in methods of assessment, investigation, and management.…”
Section: Editor's Notementioning
confidence: 98%
“…30,31 The following study characteristics were extracted from the articles: design of the study, number of patients, type of intervention, effects on the awareness, and functional outcome measures. The overall effect of each intervention was summarized as positive (+), no effect (0), or negative (−).…”
Section: Data Extractionmentioning
confidence: 99%